A Different Geography: Tuning In, Stretching Geography, and Centering Life - Jacobsen, Malene H. (ACME, 2026)
In this piece, I suggest that a critical geography must be curious about how we can do geography differently in order to collectively work towards a more inclusive and just discipline. I build on geographers’ critique of the discipline, including its ties to colonialism and imperialism, its role in producing and maintaining racialized hierarchies, and the continued sidelining of particular critical approaches, theories, and epistemologies. More specifically, I return to the concept of a feminist geopolitics of living as well as work by abolitionist scholars and activists as I explore how critical geography needs to be a geography that is driven by a critical imperative, yet attentive the ways in which how people make lives, assert rights, and build alternative futures collectively in order to make different geographies visible. In conclusion, I argue that a critical geography must include an experimental expansion of our political imagination and praxis.